Projecting the Intramural ASEAN Norms into Extramural Terrain - Constructivism: Does TAC Work in the South China Sea? - Indraswari, Ratih (Jurnal Ilmiah HUBUNGAN INTERNASIONAL, 2013)
Abstract: This article examines the role of ASEANs norms in managing dispute over the South China Sea.ASEAN shares the beliefs that the settlement of differences or disputes by peaceful means and the abandonmentof the threat or use of force are necessary to ensure the stability over the region. It attempts to analyze thepossibility of exporting this intramural norm of ASEANs model of dispute settlement into an extramural terrainand seeks to answer the question whether ASEANs norm of cooperation can alter claimants perception towardseach other, and thus in return will constrain the urge to solve the dispute by force.Keywords : ASEAN norm, ASEANs model of dispute settlements, TAC, South China Sea, China